Curriculum and school knowledge in contemporary society: challenges for the education of people with disabilities - Lunardi Mendes, Geovana Mendonça; Silva, Fabiany Cassia (Education Policy Analysis Archives, 2014)
Contemporary studies on curriculum challenge the social and scientific legitimacy of the knowledge to be taught. Confronting this historic challenge of curriculum studies appears crucial when taken together with the search for understanding of the processes of schooling for individuals with disabilities. Imbued with that challenge, this paper presents a set of reflections resulting from research carried out by the Group of Studies and Research – School Culture Monitoring (OCE) and the Centre of School Practices (OPE). Those observations aim to clarify some of the evidence that is taken as a theme for analyzing the relationship between curriculum and school knowledge in contemporary society and its implications for the education of people with disabilities. In this context, our research agenda seeks to reconfigure the ongoing investigation of school practices and discourses and their relationship with knowledge.